2008
DOI: 10.1128/jb.01412-07
|View full text |Cite
|
Sign up to set email alerts
|

Phage Response to CRISPR-Encoded Resistance in Streptococcus thermophilus

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR) and their associated genes are linked to a mechanism of acquired resistance against bacteriophages. Bacteria can integrate short stretches of phage-derived sequences (spacers) within CRISPR loci to become phage resistant. In this study, we further characterized the efficiency of CRISPR1 as a phage resistance mechanism in Streptococcus thermophilus. First, we show that CRISPR1 is distinct from previously known phage defense systems and is effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
1,168
5
16

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,131 publications
(1,282 citation statements)
references
References 40 publications
(55 reference statements)
42
1,168
5
16
Order By: Relevance
“…Further sequencing of the phage genomes revealed that the phage had mutated so that their sequence was no longer identical to the spacers 21 . Resistant phage having sequences identical to spacers were also isolated, but the AGAA downstream recognition motif was mutated in their genome, further strengthening the hypothesis that this motif is important for CRISPR function 49 . The selective pressure imposed by CRISPR on the phage therefore leads to rapid changes in their genome, and provides a glimpse into how CRISPR might be involved in driving the extremely high evolutionary rates observed in phage.…”
Section: Crispr Is An Anti-phage Defence Systemmentioning
confidence: 67%
See 2 more Smart Citations
“…Further sequencing of the phage genomes revealed that the phage had mutated so that their sequence was no longer identical to the spacers 21 . Resistant phage having sequences identical to spacers were also isolated, but the AGAA downstream recognition motif was mutated in their genome, further strengthening the hypothesis that this motif is important for CRISPR function 49 . The selective pressure imposed by CRISPR on the phage therefore leads to rapid changes in their genome, and provides a glimpse into how CRISPR might be involved in driving the extremely high evolutionary rates observed in phage.…”
Section: Crispr Is An Anti-phage Defence Systemmentioning
confidence: 67%
“…Two recent studies have reported on a short motif present in phage genomes 1-2 nucleotides downstream to spacer-matching sequences [49][50] . This motif was hypothesized to be important for recognition, or cleavage, of phage sequences by the CRISPR system.…”
Section: Structural Features Of Crispr Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the E. coli Type I-E CRISPR-Cas system, DNA from invading viruses is inserted into a genomic CRISPR array in 33-base units termed spacers 11 . The sequences from which spacers are derived are termed protospacers 12 . Here, we began with an image (Extended Data Fig.…”
mentioning
confidence: 99%
“…Additionally, the specificity of the resistance was demonstrated to be directly related to the sequence of the spacers, which are derived from DNA strands of phage open reading frames [7]. This was further supported by Deveau and colleagues, through studies of phage responses in Streptococcus thermophilus which demonstrated that CRISPR confers phage resistance [36].…”
Section: Discovery Of Crispr-casmentioning
confidence: 79%